2020
DOI: 10.1093/pubmed/fdaa214
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of 14 to 17-year old adolescents’ views of early and preventative mental health support in schools

Abstract: Background Preventative interventions may be effective in reducing and preventing symptoms of mental ill health in children and young people. However, there is a paucity of research in this area that explores the views of young people. This paper reports on a qualitative study to inform the future development of attractive and appropriate early and preventative school-based mental health interventions. Methods Semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As part of this, we will identify potential facilitators and barriers to implementation of WSAs, and provide guidance on operational definitions of WSAs, assessment methods and evaluation. There also continues to be a need for work with young people to better understand what acceptable, effective preventative school-based mental health support looks like, and to improve access to services at the school level (Spencer et al, 2020). The findings from this evaluation will help to inform local commissioners’ transformation plans, and improve services across the NHS, social care and the third sector.…”
Section: Discussionmentioning
confidence: 99%
“…As part of this, we will identify potential facilitators and barriers to implementation of WSAs, and provide guidance on operational definitions of WSAs, assessment methods and evaluation. There also continues to be a need for work with young people to better understand what acceptable, effective preventative school-based mental health support looks like, and to improve access to services at the school level (Spencer et al, 2020). The findings from this evaluation will help to inform local commissioners’ transformation plans, and improve services across the NHS, social care and the third sector.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Nepal in a rural area among school children reported issues such as addictive behaviour, not paying attention to studies, getting angry over small issues, fighting back, disobedience, and stealing (11). In a study conducted among students aged 14-17 years in North East England, Spencer et al, describe how students felt sad and depressed when they were nearing an exam and that bullying was a common problem among those students (12). A national survey conducted by UNICEF in Sri Lanka revealed that 75% of students had…”
Section: Discussionmentioning
confidence: 99%
“…Senanayake et al, report the association of violence with tobacco and alcohol among 13 to 17year-old Sri Lankan students (14). Sri Lankan, as well as global studies, have reported that poverty, alcohol and substance use, distorted family relationships, low education level of the parents, lack or excessive attention of the parents and domestic violence were associated with mental health problems of the students (11,12). In addition, Somasundaram has highlighted the impact of the civil war on the mental well-being of adolescents in Sri Lanka (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A useful and complementary construct to assist in developing such interventions is mental health literacy (MHL), defined as: “understanding how to obtain and maintain positive mental health, understanding mental disorders and their treatments, decreasing stigma related to mental disorders, and, enhancing help-seeking efficacy” (Kutcher et al , 2016b, p. 155). Adolescents often demonstrate poor MHL, with recent evidence suggesting that mental health education is not always sufficiently addressed within schools (Spencer et al , 2022). Poor MHL leads to limited help-seeking behaviours, which poses a challenge to successful early intervention (Goodwin et al , 2021; Sinclair and Holden, 2013).…”
Section: Introductionmentioning
confidence: 99%